2017
DOI: 10.18697/ajfand.77.16560
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable agriculture: Developing a common understanding for modernization of agriculture in Africa

Abstract: The concept of sustainability has become central to all sectors all over the world, from agriculture to environment to business, engineering and industrialization. The principle of sustainability is the same all over these sectors. However, the understanding of the term may vary from sector to sector depending on how it may be applied to a specific sector. Sustainable agriculture is a term that continues to gain prominence in the agricultural sector but not without lots of misunderstanding, controversy and cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…The scientific foundations of production in the AIC in the conditions of Industry 4.0 are set in the concept of AIC 4.0 (Agriculture 4.0) and are considered in the works Altukhov et al (2019), Belenkova et al (2018), Bogoviz et al (2018), Butorin and Bogoviz (2019), Kansanga et al (2019), Ogemah (2017), Polyakova et al (2019), Sergi et al (2019a), Sergi et al (2019b), Sibirskaya et al (2017) and Weltzien (2016). The current role of education during placement of production in the AIC is studied in the publications such as De Castro and Saes (2018), Popkova (2019), Popkova et al (2017a), Popkova et al (2017b) and Yost et al (2019).…”
Section: Methodsmentioning
confidence: 99%
“…The scientific foundations of production in the AIC in the conditions of Industry 4.0 are set in the concept of AIC 4.0 (Agriculture 4.0) and are considered in the works Altukhov et al (2019), Belenkova et al (2018), Bogoviz et al (2018), Butorin and Bogoviz (2019), Kansanga et al (2019), Ogemah (2017), Polyakova et al (2019), Sergi et al (2019a), Sergi et al (2019b), Sibirskaya et al (2017) and Weltzien (2016). The current role of education during placement of production in the AIC is studied in the publications such as De Castro and Saes (2018), Popkova (2019), Popkova et al (2017a), Popkova et al (2017b) and Yost et al (2019).…”
Section: Methodsmentioning
confidence: 99%
“…and the advantages of AIC 4.0 as a means of rationalization of agricultural production are emphasized in the works Weltzien, C. (2016), Butorin and Bogoviz (2019), and Altukhov et al (2019). The necessity for state stimulation of scientific& technical development as a means of increasing the effectiveness and competitiveness of the AIC on the basis of cases that reflect successful practical experience of various countries of the world is substantiated in the work Kansanga et al (2019) by the example of Ghana and New Zealand and in Ogemah (2017) by the example of African countries. As a result of the literature review, it is possible to conclude that though the separate distinguished blocks of scientific knowledge are rather elaborated, there's no systemic opinion on the problem of quality management in the AIC on the basis of territorial-sectoral placement and scientific& technical development in the modern economic science.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition to the aforementioned factors, this study argues that the available empirical literature on the impacts of adopting SAPs remains inconclusive. Previous studies have shown substantial contributions of adopting SAPs in production, household income, and food security (Adenle et al, 2019;Bekele et al, 2021;Bongole et al, 2021;Ehiakpor et al, 2021;Kassie et al, 2013;Ma & Wang, 2020;Manda et al, 2016;Ndiritu et al, 2014;Ogemah, 2017;Zhou et al, 2018;Rose et al, 2019;Zeweld et al, 2020). However, the is insufficient literature on the impact of adopting multiple SAPs consisting of manure, intercropping, crop residual, improved maize varieties, and crop rotation on food security, nutrition, and poverty in Tanzania.…”
Section: Introductionmentioning
confidence: 98%